Diffusion Tensor Imaging and Neurobehavioral Outcome in Children With Brain Tumors Treated With Chemotherapy. (March 2016) - Baron Nelson, Mary; Compton, Peggy; Macey, Paul M.; Patel, Sunita K.; Jacob, Eufemia; O'Neil, Sharon; Ogren, Jennifer; Finlay, Jonathan L.; Harper, Ronald M.
Background . Childhood brain tumor survivors (CBTS) often experience treatment-related neurocognitive deficits affecting quality of life (QOL), but systemic chemotherapy contributions to outcomes are unclear. Our objective was to relate brain tissue changes to neurocognitive and QOL effects after systemic myeloablative chemotherapy with autologous hematopoietic progenitor cell rescue in CBTS. Procedure. Regional brain volumes and diffusion tensor indices were correlated with neurocognitive, behavioral, and QOL measures, and compared between 8 CBTS (mean age 8.5 years, mean age at diagnosis 32 months), and 9 healthy controls (mean 9.3 years). Results . Overall QOL, school, and psychosocial functioning were significantly lower in patients ( P < .05). Most patients scored within normative ranges on neurocognitive and behavioral assessment. Elevated mean diffusivity and decreased fractional anisotropy, indicating gray and white matter injury, respectively, appeared in memory and executive functioning areas. Low scores on Inhibition on the Neuropsychological Assessment–II were correlated with elevated mean diffusivity in prefrontal cortex. Conclusions. Brain injury, decreased QOL, and to a lesser extent, executive functioning deficits appear in CBTS treated with myeloablative chemotherapy and autologous hematopoietic progenitor cell rescue. Early cognitive and psychological assessment and intervention are warranted in this population.